IDEAŁ WŁADCY I JEGO RODZINY NA PODSTAWIE MÓW POGRZEBOWYCH KU CZCI TEODOZJUSZA l, FLACYLLI I PULCHERII - Twardowska, Kamilla (In Gremium. Studies in History, Culture and Politics, 2011)
THE PARAGON OF A RULER AND HIS FAMILY BASED ON THE FUNERAL SPEECHES IN HONOUR OF THEODOSIUS I, FLACCILLA, AND PULCHERIA Theodosius I is well known to historians. He was a great leader and a ruler, who made Christianity the main religion of the empire. Funeral speeches in his, his wife Flaccilla’s and his daughter Pulcheria’s honor were created and are important sources in research concerning the changes in mentality and customs of people at the end of the 4th century.